Effects of oleoylethanolamide supplementation on inflammatory biomarkers, oxidative stress and antioxidant parameters of obese patients with NAFLD on a calorie-restricted diet: A randomized controlled trial - Tutunchi, Helda; Zolrahim, Farideh; Nikbaf-Shandiz, Mahlagha; Naeini, Fatemeh; Ostadrahimi, Alireza; Naghshi, Sina; Salek, Reza; Najafipour, Farzad (Frontiers in Pharmacology, 2023)
Background Oxidative stress is considered a major factor in the pathophysiology of non-alcoholic liver disease (NAFLD). A growing body of evidence indicates that oleoylethanolamide (OEA), a bioactive lipid mediator, has anti-inflammatory and antioxidant properties. This trial investigated the effects of OEA administration on inflammatory markers, oxidative stress and antioxidant parameters of patients with NAFLD. Methods The present randomized controlled trial was conducted on 60 obese patients with NAFLD. The patients were treated with OEA (250 mg/day) or placebo along with a low-calorie diet for 12 weeks. Inflammatory markers and oxidative stress and antioxidant parameters were evaluated pre-and post-intervention. Results At the end of the study, neither the between-group changes, nor the within-group differences were significant for serum levels of high-sensitivity C-reactive protein (hs-CRP), interleukin-1 beta (IL-1β), IL-6, IL-10, and tumor necrosis-factor α (TNF-α). Serum levels of total antioxidant capacity (TAC) and superoxide dismutase (SOD) significantly increased and serum concentrations of malondialdehyde (MDA) and oxidized-low density lipoprotein (ox-LDL) significantly decreased in the OEA group compared to placebo at study endpoint (p=0.039, 0.018, 0.003 and 0.001, respectively). Although, no significant between-group alterations were found in glutathione peroxidase and catalase. There were significant correlations between percent of changes in serum oxidative stress and antioxidant parameters with percent of changes in some anthropometric indices in the intervention group. Conclusion OEA supplementation could improve some oxidative stress/antioxidant biomarkers without any significant effect on inflammation in NAFLD patients. Further clinical trials with longer follow-up periods are demanded to verify profitable effects of OEA in these patients.